Adverse drug reactions induced by cotrimoxazole: Still a lot of preventable harm. (16th November 2021) - Coppry, Maïder; Duret, Stéphanie; Berdaï, Driss; Miremont‐Salamé, Ghada; Fourrier‐Réglat, Annie; Haramburu, Françoise; Rogues, Anne‐Marie; Noize, Pernelle
Abstract: Owing to a broad spectrum and low cost antimicrobial, cotrimoxazole is largely prescribed. However, its use is associated with various adverse drug reactions (ADRs) that warrant to ensure rational prescribing. This study aimed to describe spontaneous reports of cotrimoxazole ADRs and to evaluate the quality of prescription in patients who had ADRs. Suspected cotrimoxazole‐induced ADRs cases reported to the Bordeaux regional pharmacovigilance center (France) during a 5‐year period were described. Seriousness was assessed according to international criteria. Quality of prescription was assessed by compliance with the Summary of Product Characteristics (SPC) and relevance of cotrimoxazole indication. Then, an ADR was considered as preventable if the cotrimoxazole indication was not relevant, or potentially preventable if indication was relevant but the prescription was not compliant with the SPC. A total of 96 cases were analyzed: median age was 60.5 years (range: 4–94); 59.4% of patients were male. ADRs were mostly cutaneous disorders ( n = 46) and hematological disorders ( n = 25). A total of 60 serious ADRs occurred in 55 patients. Prescribers complied with all SPC recommendations in 21.9% of cases. Indication of cotrimoxazole was relevant or highly relevant in 41 cases. In 58% of cases, the occurrence of a cotrimoxazole‐induced ADR would have been preventable or potentially preventable. In a context of increasing interest for this antibiotic to treat infections due to resistant bacteria, physicians should be more aware of the potential consequences of inappropriate prescribing cotrimoxazole and reserve its use when there is no alternative and under suitable monitoring.